Unmasking the Culprit: Successful Restoration of Menstrual Function in a Case of Secondary Amenorrhea Due to Tuberculous Endometritis Mimicking Polycystic Ovary Syndrome - Riyan Hari Kurniawan; Muhammad Syauqi Mirza; Ilham Utama Surya; Muhammad Dwi Priangga; Cepi Teguh Pramayadi; Herbert Situmorang; Eka Rusdianto Gunardi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Secondary amenorrhea presents a significant diagnostic challenge in gynecology. While Polycystic Ovary Syndrome (PCOS) is a common cause, rare etiologies like tuberculous endometritis can be overlooked, especially in patients with features suggestive of PCOS. This phenomenon, known as diagnostic overshadowing, can lead to delayed diagnosis and irreversible reproductive consequences. Case presentation: A 35-year-old nulligravid woman with a diagnosis of Class I Obesity presented with a five-year history of secondary amenorrhea and a desire for fertility. Her clinical and initial ultrasonographic findings were suggestive of PCOS. However, persistent amenorrhea despite hormonal therapy prompted further investigation. Hysteroscopy revealed a fibrotic uterine cavity with micropolyps, and subsequent endometrial biopsy with histopathology, polymerase chain reaction (PCR), and culture confirmed a diagnosis of tuberculous endometritis. The patient was successfully treated with a six-month anti-tuberculosis regimen, cyclical progestin therapy, and a structured lifestyle modification program. Following treatment, she experienced a significant weight loss, resumption of regular menstrual cycles, and marked improvement in endometrial and ovarian ultrasound parameters. Conclusion: This case underscores the critical importance of a comprehensive diagnostic evaluation for secondary amenorrhea, including endometrial sampling, even when a common diagnosis like PCOS is suspected. It highlights the potential for tuberculous endometritis to mimic PCOS and demonstrates the efficacy of a multidisciplinary approach in restoring menstrual and potentially reproductive function. Clinicians in tuberculosis-endemic regions must maintain a high index of suspicion for this insidious pathology to prevent long-term morbidity.